2020
DOI: 10.21203/rs.3.rs-16844/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Extended Spectrum Beta-Lactamase Producing Bacteria (ESBL) in Patients presenting with Urinary Tract Infections (UTIs) at a peri-Urban hospital, Uganda

Abstract: Introduction Urinary tract infections remain one of the infections that are commonly diagnosed in Uganda with Enterobacteriaceae reported as the commonest uropathogens. Extended Spectrum Beta Lactamase producing Enterobacteriaceae have emerged as significant pathogens responsible for most of these urinary tract infections throughout the world. This resistance often leads to therapeutic failures from multidrug resistant bacteria. This study was carried out to determine the prevalence of Extended Spectrum Beta-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In Uganda, studies show a high prevalence of the ESBL among patients with UTIs [8][9][10] Individuals dwelling in refugee settlements face numerous socio-economic, hygiene, and health care challenges [11]. These predispose to high-risk behaviors which may augment acquiring Urinary Tract Infections [12] In Uganda, the United Nations High Commission for Refugees (UNHCR) health report indicated that 2% of the consultations registered in health centers in refugee settlements are empirically treated for Urinary Tract Infections [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, studies show a high prevalence of the ESBL among patients with UTIs [8][9][10] Individuals dwelling in refugee settlements face numerous socio-economic, hygiene, and health care challenges [11]. These predispose to high-risk behaviors which may augment acquiring Urinary Tract Infections [12] In Uganda, the United Nations High Commission for Refugees (UNHCR) health report indicated that 2% of the consultations registered in health centers in refugee settlements are empirically treated for Urinary Tract Infections [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, studies show a high prevalence of the ESBL among patients with UTIs [8-10] Individuals dwelling in refugee settlements face numerous socio-economic, hygiene, and health care challenges [11]. These predispose to high-risk behaviors which may augment acquiring Urinary Tract Infections [12]…”
Section: Introductionmentioning
confidence: 99%